Lactoferrin as Immune-Enhancement Strategy for SARS-CoV-2 Infection in Alzheimer’s Disease Patients - Fernando Bartolomé; Fernando Bartolomé; Luigi Rosa; Piera Valenti; Francisco Lopera; Jesús Hernández-Gallego; Jesús Hernández-Gallego; Jesús Hernández-Gallego; José Luis Cantero; José Luis Cantero; Gorka Orive; Gorka Orive; et al. (Frontiers in Immunology, 2022)
Coronavirus 2 (SARS-CoV2) (COVID-19) causes severe acute respiratory syndrome. Severe illness of COVID-19 largely occurs in older people and recent evidence indicates that demented patients have higher risk for COVID-19. Additionally, COVID-19 further enhances the vulnerability of older adults with cognitive damage. A balance between the immune and inflammatory response is necessary to control the infection. Thus, antimicrobial and anti-inflammatory drugs are hopeful therapeutic agents for the treatment of COVID-19. Accumulating evidence suggests that lactoferrin (Lf) is active against SARS-CoV-2, likely due to its potent antiviral and anti-inflammatory actions that ultimately improves immune system responses. Remarkably, salivary Lf levels are significantly reduced in different Alzheimer’s disease (AD) stages, which may reflect AD-related immunological disturbances, leading to reduced defense mechanisms against viral pathogens and an increase of the COVID-19 susceptibility. Overall, there is an urgent necessity to protect AD patients against COVID-19, decreasing the risk of viral infections. In this context, we propose bovine Lf (bLf) as a promising preventive therapeutic tool to minimize COVID-19 risk in patients with dementia or AD.